MAKNA TARI GANDHONG DI DESA BANGUN KECAMATAN MUNJUNGAN KABUPATEN TRENGGALEK - Melinia Intan Pramadani; Setya Widyawati (Greget, 2021)
The thesis entitled The Meaning of Gandhong Dance in Bangun Village, Munjungan District, Trenggalek Regency reveals the problems of meaning of the Gandhong Dance. These  three  problems  are  studied  by  performing  arts  theory  and  pragmatics theory. In its application to analyze the form of the nonverbal component using the theory of performing arts according to Maryono and the analysis of the form of the verbal component using a pragmatic approach with Kreidler's speech act theory. The research method is qualitative in nature with data collection by direct observation or through recording media, interviews, and literature studies. The results of the research findings based on the discussion and linkage of nonverbal components, verbal components, and audience responses that Gandhong Dance is a folk dance that functions as entertainment and provides meaning messages that are conveyed to the audience. The meaning of Gandhong Dance is to show the value of social life by living in harmony, mutual cooperation, maintaining health, and praying for safety and peace.